Synthesis and Characterization of Dicobalt-Iron Complex (μ3-S)FeCo2(CO)7[P(m-MeC6H4)3]2 - Gao, Wei (Asian Journal of Chemistry, 2015)
Treatment of dicobalt-iron complex (μ3-S)FeCo2(CO)9 (1) with P(m-MeC6H4)3 in CH2Cl2 afforded the dicobalt-iron complex (μ3-S)FeCo2(CO)7[P(m-MeC6H4)3]2 (2) in 49 % yield. The new complex 2 was structurally characterized by IR, 1H NMR, 31P{1H} NMR and 13C{1H} NMR spectroscopy.